Termination of pregnancy after non-invasive prenatal testing (NIPT): ethical considerations - Shakespeare, T; Hull, R (University of Oxford, Oxford Uehiro Centre for Practical Ethics, 2018)
This article explores the Nuffield Council on Bioethics’ recent report about non-invasive prenatal testing. Given that such testing is likely to become the norm, it is important to question whether there should be some ethical parameters regarding its use. The article engages with the viewpoints of Jeff McMahan, Julian Savulescu, Stephen Wilkinson and other commentators on prenatal ethics. The authors argue that there are a variety of moral considerations that legitimately play a significant role with regard to (prospective) parental decision-making in the context of NIPT, for example, views on the morality of abortion and understandings of the impact of disability on quality of life. The variable nature of such considerations, both singularly and combined, suggests that any approach to NIPT should be sensitive to and understanding of similarly variable parental assessments and decisions. The implications of the approach developed for current and future policies in this area are explored, along with the impact of such arguments on ideas about procreative beneficence.